2021
DOI: 10.1021/acs.orglett.1c00820
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Free Radical Thiocyanatosulfonation of Terminal Alkynes in Aqueous Medium

Abstract: Here we report a novel and practical approach for preparing (E)-β-(thiocyanato)­vinyl sulfones through the 1,2-thiocyanatosulfonation of terminal alkynes with NH4SCN and sulfonyl hydrazides. Advantages of this reaction include mild conditions, the absence of metal, readily available reagents, a broad substrate scope, good functional group compatibility, and excellent stereoselectivity. The radical species-induced pathway is also demonstrated by mechanistic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 63 publications
1
26
0
1
Order By: Relevance
“…A one-step three-component reaction is highly desired given its convenience and high efficiency. 7,55,56 Considering the general structure in the listed drugs (Figure S2) and encouraged by the results achieved above, a practical application of 1b was attempted by making use of the classical Petasis reaction (Scheme 2, see the Supporting Information). 7 So, 1b was treated with a hydrolysis process to obtain (E)-βstyrene boronic acid and then reacted with 1-benzhydrylpiperazine (13) and paraformaldehyde to give cinnarizine in a yield of 81%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A one-step three-component reaction is highly desired given its convenience and high efficiency. 7,55,56 Considering the general structure in the listed drugs (Figure S2) and encouraged by the results achieved above, a practical application of 1b was attempted by making use of the classical Petasis reaction (Scheme 2, see the Supporting Information). 7 So, 1b was treated with a hydrolysis process to obtain (E)-βstyrene boronic acid and then reacted with 1-benzhydrylpiperazine (13) and paraformaldehyde to give cinnarizine in a yield of 81%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[5] Zhang et al reported a thiocyanatosulfonation of terminal alkynes with NH 4 SCN and sulfonyl hydrazides to access (E)-β-(thiocyanato)vinyl sulfones. [6] Xu et al reported a thiosulfonates of aryl alkynes to deliver (E)-(β)-arylthiolvinyl sulfones exclusively. [7] Despite these advances, thiosulfonylation of alkynes involving the formation of C À SO 2 and another C À SO bond simultaneously has only one example.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, we and Tang et al finished copper(I)/bromodifluoroacetate‐co‐catalyzed and iodine(III) reagent‐mediated disulfonation of alkynes with sodium arylsulfinates, respectively [5] . Zhang et al reported a thiocyanatosulfonation of terminal alkynes with NH 4 SCN and sulfonyl hydrazides to access (E)‐β‐(thiocyanato)vinyl sulfones [6] . Xu et al reported a thiosulfonates of aryl alkynes to deliver (E)‐(β)‐arylthiolvinyl sulfones exclusively [7] .…”
Section: Introductionmentioning
confidence: 99%
“… However, the radical addition reaction of CBr 4 with an alkyne is still vey rare . As part of our continuous studies on the radical-promoted difunctionalization of alkynes, we question whether a radical interaction between CBr 4 and an alkyne could be achieved. The radical additions to alkynes is one prior method to the synthesis of functional alkenes, but the challenge is the highly reactive vinyl radical intermediate formed in the process .…”
mentioning
confidence: 99%